2011
DOI: 10.1080/03079457.2011.617725
|View full text |Cite
|
Sign up to set email alerts
|

Replication ability of three highly protective Marek's disease vaccines: implications in lymphoid organ atrophy and protection

Abstract: The present work is a chronological study of the pathogenesis of three attenuated serotype 1 Marek's disease (MD) virus strains (RM1, CVI988 and 648A80) that provide high protection against MD but have been attenuated by different procedures and induce different degrees of lymphoid organ atrophy. All studied strains replicated in the lymphoid organs (bursa,x thymus and spleen) and a peak of replication was detected at 6 days post inoculation (d.p.i.). Differences, however, were observed among vaccine strains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The genomes of these strains are highly similar to the oncogenic strains, but crucial differences exist . The MD vaccine viruses replicate in host cells and transmit to other birds [Baigent et al, 2005;Islam et al, 2007;Tan et al, 2007;Gimeno et al, 2011;Islam et al, 2013;], but do not induce disease or lymphomas [Calnek and Witter, 1997]. Despite improved understanding of vaccine-related immunity [Witter, 1984;Osterrieder et al, 2006], an explanation for the anti-tumor effect of vaccination has not yet been established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genomes of these strains are highly similar to the oncogenic strains, but crucial differences exist . The MD vaccine viruses replicate in host cells and transmit to other birds [Baigent et al, 2005;Islam et al, 2007;Tan et al, 2007;Gimeno et al, 2011;Islam et al, 2013;], but do not induce disease or lymphomas [Calnek and Witter, 1997]. Despite improved understanding of vaccine-related immunity [Witter, 1984;Osterrieder et al, 2006], an explanation for the anti-tumor effect of vaccination has not yet been established.…”
mentioning
confidence: 99%
“…In the MDV infection cycle, oncogenic strains transition from a cytolytic replication stage, during which the viral genome takes an episomal and extrachromosomal form, to a latent stage, characterized by evasion of host immune responses Adldinger and Calnek, 1973;Baigent and Davison, 2004;Osterrieder et al, 2006;Arumugaswami et al, 2009;Gimeno et al, 2011] with the latter having a temporal overlap with MDV-host telomere integration events [Robinson et al, 2010[Robinson et al, , 2014 and decline in the quantity of extrachromosomal MDV genomes [Kaschka-Dierich et al, 1979;Delecluse and Hammerschmidt, 1993]. Latently infected host CD4 T lymphocytes are the target cell population for transformation events and subsequent lymphoma development, around 2-3 weeks after infection in susceptible birds [Witter, 1984;Calnek, 2001;Burgess and Davison, 2002;Nair, 2005;Trapp et al, 2006].…”
mentioning
confidence: 99%
“…Therefore, the non-oncogenic HVT may provoke higher IL-10 expression. Meanwhile, the proposed higher replication of Rispens strain over the HVT one in the thymus tissue as suggested by Gimeno et al, (2011) may provide an explanation for the non-significant difference in IL-10 expression in the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Gimeno et al, (2011) showed that the CVI988 strain replicates in the bursa and thymus and its viral DNA can be detected in those organs by the day 6 post s/c inoculation, then this replication decline toward the day 14 followed by a second replication wave as recorded in their following examination time point at 26 days. Their results also revealed that CVI-988 viral DNA load in thymus was higher than in bursa.…”
Section: Discussionmentioning
confidence: 99%
“…RM1 was determined to be attenuated and replicated efficiently in vivo, yet failed to cause MD and was typified by severe BTA (Jones et al, 1996). Further characterization revealed that not only was the attenuated RM1 virus very protective as a vaccine, but also exhibited high tissue tropism for early dissemination and replication to the thymus (Gimeno et al, 2011). Among several vaccine viruses examined, RM1 showed the earliest and highest replication within lymphoid organs, specifically the thymus, compared to the vaccine viruses that did not cause BTA.…”
Section: Discussionmentioning
confidence: 99%